Reasons for Attempted Suicide in Europe: Prevalence, Associated Factors, and Risk of Repetition. Issue 1 (2nd January 2016) - Burón, P.; Jimenez-Trevino, L.; Saiz, P. A.; García-Portilla, M. P.; Corcoran, P.; Carli, V.; Fekete, S.; Hadlaczky, G.; Hegerl, U.; Michel, K.; Sarchiapone, M.; Temnik, S.; et al.
Abstract : To examine the prevalence of specific reasons for attempted suicide, factors associated with them, and whether reasons for attempted suicide influence risk of repetition. As part of the Monitoring Suicide in Europe (MONSUE) project, data on 4, 683 suicide attempters from nine European countries were collected. Independence tests were used to study the influence of age, gender, and other factors on reported reasons. We examined risk of repetition using logistic regression analysis. Interpersonal conflict was common for all patients except those widowed, living alone, or retired. Mental health problems were prevalent among over 45 year-olds, patients unable to work, and patients with a history of at least three suicide attempts. Financial difficulties were cited more often by patients who were 45–64 years old, divorced or separated, living with children only, and unemployed. Close bereavement/serious illness and own physical illness were associated with those over 65 years of age. Two reasons for suicide attempt, interpersonal conflict and mental health problems, were associated with increased risk of repetition independent of other factors. Suicide attempters have a multitude of problems of varying prevalence depending on age, gender, and other factors. They present a range of clinical profiles that require a multidisciplinary response.